Multiple-job holding is not a type of precarious employment - Bouwhuis, Stef; Geuskens, Goedele A; van der Beek, Allard J; Boot, Cécile RL (Scandinavian Journal of Work, Environment & Health, 2019)
We are writing in regards to the review by Koranyi et al (1) on precarious employment and occupational accidents and injuries. In the review, multiple-job holding was classified as a type of precarious employment. In this letter, we argue multiple-job holding should not be considered a type of precarious employment and that multiple-job holders constitute a heterogeneous group of workers. In their review, Koranyi et al defined precarious employment as “uncertainty as to the duration of employment, multiple possible employers or a disguised or ambiguous employment relationship, a lack of access to social protection and benefits usually associated with employment, low pay, and substantial legal and practical obstacles to joining a trade union and bargaining collectively” (1). In this ILO definition, multiple-job holding is presented as a type of precarious employment. Most researchers now agree that precariousness, on the one hand, is a multi-dimensional construct, including at least four dimensions: (i) employment instability; (ii) low material rewards; (iii) control over working conditions and pace of work; and (iv) a lack of social rights and protections (2‒4). Multiple-job holding, on the other hand, is defined in the scientific literature as having two or more jobs. It does not relate to the quality of the terms of employment associated with these jobs. Previous research has shown that employees without a permanent contract are more likely to have multiple jobs (5,6). This, however, does not mean that multiple-job holding is equivalent to precarious employment. Firstly, precariousness has many dimensions, and encompasses more than "just" having a temporary contract. Secondly, multiple-job holders are a heterogeneous group of workers (7): not all multiple-job holders have temporary contracts in one or more of their jobs. Recent research on multiple-job holding has made significant progress in exploring its heterogeneity. Rouault conceptualized, but not empirically studied, four groups of multiple-job holders (8). Another study, conducted by the authors of the present letter (9), distinguished four groups using latent class analysis among 702 multi-jobbers: (i) vulnerable; (ii) indifferent; (iii) satisfied combination; and (iv) satisfied hybrid multiple-job holders. The vulnerable group was exposed to more dimensions of precariousness than the other three groups. These workers more often combined jobs with temporary contracts, for instance. Furthermore, the vulnerable multiple-job holders more often reported low autonomy and a relatively high percentage of these workers reported that their household was short of money. Cross-sectional analyses showed that the vulnerable group, on average, experienced worse physical and mental health than the three other groups of multiple-job holders (9). In contrast to this vulnerable group of multiple-job holders, other groups of multiple-job holders experienced benefits from holding multiple jobs (9). These findings have been confirmed in a qualitative study in which we found that some multi-jobbers only experienced benefits of multiple-job holding, eg, positive spill-over effects between jobs: networks established or skills learned in one job that can be used in others (10). Marucci-Wellman acknowledged the heterogeneity of multiple-job holders in her editorial on the review by Koranyi et al (11). She underscored the importance of distinguishing groups of multiple-job holders stating that, if we treat multiple-job holders as one group, health effects for the most vulnerable group may be obscured. We would argue that multiple-job holding as such should never be regarded as equivalent to precarious employment, even if a multiple-job holder has one or more jobs that can be considered precarious. Given the increasing prevalence of precarious employment and multiple-job holding as well as their potential health effects, future research on these issues is crucial. We recommend to use clear definitions of precarious employment and multiple-job holding. We propose that precariousness refers to the terms of employment and working conditions of a job, whereas multiple-job holding refers to the number of jobs a worker has, regardless of actual employment and working conditions. To conclude, it is possible, but by no means necessary, that one or more of the jobs held by a multi-job holder can be considered precarious. In fact, for some multiple-job holders, the combination of two precarious jobs may have benefits. Therefore, it is important not to study multiple-job holding as a type of precarious employment and additionally to take the heterogeneity among multiple-job holders into account in future research.
Keywords: multi-jobber; multiple job holding; multiple jobs; multiple-job holding; precarious employment